Effectiveness of Day Care Services of Karaj Kahrizac Rehabilitation Center on Activities of Daily Living Among Older People, 2010 April-2011 March - Mohsen Rahimi; Reza Fadaye Vatan; Keyvan Davatgaran; Akbar Biglarian; Marziye Shirazikhah; Mehrnoush Boroomandpoor; Robab Sahaf (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: Day care centers try to give day care services to old people to improve their functional abilities and inhibit their unnecessary admition in residential care centers. The main object of this study was investigating the effectiveness of day care services of Karaj Kahrizac Rehabilitation Center on activities of daily living among old People in 2010 April-2011 March who had been received the services for 6 months. Methods & Materials: A pretest-posttest study was designed on the files documents of 71 old persons admitted in the center. The method of sampling was head counting and Barthel Index and Lawton Scale were used as the study tools Then the evaluation scores of “basic & instrumental activities of daily living”, before and after receiving the daily care services were compared together. Descriptive statistics, T-test, analysis of variances and analysis of co-variances were used for data analysis. P-values less than 0.05 were considered significant. Results: there was no significant difference between the mean of the basic activities of daily living scores, before and after receiving the daily care services of the center (P=0.095). Whereas there was significant difference between the mean of the instrumental activities of daily living scores, before and after receiving the daily care services of the center (P<0.001). Other findings were: High pre-services ADL scores (70% of participants with the least ADL dependency and 30% with mild dependency), proportional lower age mean, high female: men ratio (3:1), restricted use of mobility rehabilitation aids and no significant difference between the mean of pre-services ADL scores of different age groups. Conclusion: This study showed that the daily care services can improve the level of activities of daily living in the old people. However it seems that the accessibility of the olds with lower ADL scores to the center was more limited and on the other hand the main cause of referring to the center might be using of the psychological, social or leisure time services.